Exploring Stress, Psychological Well-being, and Quality of Life among Caregivers of Thalassemia Children - Mufti, Sarah; Dr. Misbah Arshad; Dania Tur Rehman (Journal of Peace, Development and Communication, 2024)
This cross-sectional correlational study explored the relationship of stress, psychological wellbeing, and quality of life among caregivers of children with thalassemia. The sample of one hundred and fifty participants were selected using convenient sampling from Sundas Foundation in Gujrat and Gujranwala cities. The data was collected by using three separate measures on Perceived Stress Scale (Kausar et al., 2019), Ryff Scale Psychological Wellbeing (Ryff, 1989), and Singapore Caregiver Quality of Life Scale (SCQOLS; Cheung et al. 2019). The results revealed the significant negative correlation of stress and well-being and quality of life among caregivers. Moreover, the findings showed that psychological well-being performed as a full mediator between psychological stress and the quality of life experienced by caregivers. The study overall suggested that the caregivers of thalassemia patients can benefit greatly from interventions that target specific stressors and provide adequate support networks. These measures, by minimizing the burden on caregivers, have the potential to improve patient care quality. The findings of this study may contribute to the development of such networks, ensuring that caregivers have the support they require to carry out their demanding tasks.